IMPLEMENTASI SISTEM MANAJEMEN KEUANGAN PENDIDIKAN - Iskandar, Jamaluddin (Idaarah: Jurnal Manajemen Pendidikan, 2019)
This paper aims to announce the implementation of finance education management. The immplemtation of school education financial management is usually carried out and implemented the functions of education financial management, especially the management of BOS funds, but is still constrained by peruses before the receipt of BOS funds and the slow disbursement of funds from determinants of policies that influence subsequent program. In accordance with this fact, the authors suggest that it is better to implement school financial management, especially in the management of BOS funds, to improve management systems in administrative management, especially in the collection of pedagogic data for completing the conditions for receiving BOS funds for schools so that plans can be implemented and the skills of the principal to find other funding sources to overcome the limited founds.